The Effect of Tourist Patients’ Experience in Marketing the Medical Tourism: An Archetypal Analytical Investigation of Al-Kafeel Hospital in Holy Karbala: Pengaruh Pengalaman Pasien Wisatawan dalam Pemasaran Pariwisata Medis: Investigasi Analitis Arketipe Rumah Sakit Al-Kafeel di Karbala Suci - Ali Abbood Awdaa (Academia Open, 2026)
General Background: Medical tourism represents one of the fastest-growing segments of the global tourism industry, contributing significantly to national economies and healthcare service development. Specific Background: Within this sector, tourist patient experience—shaped by service quality, tourism facilities, and medical services—has become central to marketing strategies and destination competitiveness. Knowledge Gap: Despite extensive discussion on medical tourism attributes, limited empirical evidence clarifies which experiential factors most strongly determine tourist loyalty in emerging destinations such as Holy Karbala. Aims: This study investigates the determinants of tourist loyalty in medical tourism marketing, focusing on the roles of tourist satisfaction, service quality, facilities, and environmental security at Al-Kafeel Hospital. Results: Based on survey data from 580 foreign tourist patients analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), the findings reveal that tourist satisfaction is the strongest predictor of loyalty (β = 0.50; f² = 0.30), followed by service quality (β = 0.35; f² = 0.18) and facilities (β = 0.28). Environmental security shows no statistically significant relationship with loyalty (p = 0.058). The structural model demonstrates strong explanatory power (R² = 0.65), with confirmed reliability and convergent validity (CR > 0.7; AVE > 0.5). Novelty: The study provides an empirically validated structural model highlighting satisfaction as the central construct in medical tourism marketing within a Middle Eastern healthcare context. Implications: The results support prioritizing service quality improvement, facility development, and systematic satisfaction monitoring to strengthen patient retention and strategic marketing performance in medical tourism destinations. Highlights• Patient contentment demonstrates the highest predictive value for repeat visitation and recommendation behavior.• Healthcare and hospitality attributes contribute significantly to behavioral commitment.• The structural model explains 65% of variance in patronage intention. KeywordsMedical Tourism; Tourist Satisfaction; Tourist Loyalty; Service Quality; PLS-SEM